Fractional flow reserve-guided revascularization: practical implications of a diagnostic gray zone and measurement variability on clinical decisions - Petraco,R; Sen,S; Nijjer,S; Echavarria-Pinto,M; Escaned,J; Francis,DP; Davies,JE (JACC. Cardiovascular interventions, 2013)
OBJECTIVES: This study sought to evaluate the effects of fractional flow reserve (FFR) measurement variability on FFR-guided treatment strategy. BACKGROUND: Current appropriateness guidelines recommend the utilization of FFR to guide coronary revascularization based on a fixed cut-off of 0.8. This rigid approach does not take into account the intrinsic biological variability of a single FFR result and the clinical judgment of experienced interventionists. METHODS: FFR reproducibility data from the landmark Deferral Versus Performance of PTCA in Patients Without Documented Ischemia (DEFER) trial was analyzed (two repeated FFR measurements in the same lesion, 10 min apart) and the standard deviation of the difference (SDD) between repeated measurements was calculated. The measurement certainty (probability that the FFR-guided revascularization strategy will not change if the test is repeated 10 min later) was subsequently established across the whole range of FFR values, from 0.2 to 1. RESULTS: Outside the [0.75 to 0.85] FFR range, measurement certainty of a single FFR result is >95%. However, closer to its cut-off, certainty falls to less than 80% within 0.77 to 0.83, reaching a nadir of 50% around 0.8. In clinical practice, that means that each time a single FFR value falls between 0.75 and 0.85, there is a chance that the FFR-derived revascularization recommendation will change if the measurement is repeated 10 min later, with this chance increasing the closer the FFR result is to 0.8. CONCLUSIONS: A measurement FFR gray-zone is found between 0.75 and 0.85]. Therefore, clinicians should make revascularization decisions based on broadened clinical judgment when a single FFR result falls within this uncertainty zone, particularly between 0.77 and 0.83, when measurement certainty falls to less than 80%.